2015
DOI: 10.1371/journal.pone.0118958
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Individual Risk Factors and Documenting the Pattern of Heat-Related Illness through Analyses of Hospitalization and Patterns of Household Cooling

Abstract: BackgroundAs climate change increases the frequency and intensity of extreme heat events researchers and public health officials must work towards understanding the causes and outcomes of heat-related morbidity and mortality. While there have been many studies on both heat-related illness (HRI), there are fewer on heat-related morbidity than on heat-related mortality.ObjectiveTo identify individual and environmental risk factors for hospitalizations and document patterns of household cooling.MethodsWe performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 58 publications
2
12
1
Order By: Relevance
“…A number of studies have shown stronger heat-related morbidity for females [52,53,54,55,56,57,58,59,60,61,62,63], but other studies have found stronger effects for males [26,29,64,65] as was found in our study. The finding of males having a significantly stronger RR than females is supported by studies of ED visits [66] and hospital admissions [64] that have shown that men are more likely than women to seek care for heat-related diagnoses [20].…”
Section: Discussioncontrasting
confidence: 67%
“…A number of studies have shown stronger heat-related morbidity for females [52,53,54,55,56,57,58,59,60,61,62,63], but other studies have found stronger effects for males [26,29,64,65] as was found in our study. The finding of males having a significantly stronger RR than females is supported by studies of ED visits [66] and hospital admissions [64] that have shown that men are more likely than women to seek care for heat-related diagnoses [20].…”
Section: Discussioncontrasting
confidence: 67%
“…Research has shown that HRI hospitalizations have increased during our study period, with more recent climate data indicating that average global temperatures continued to rise during and after the 2001 to 2010 period [ 31 , 32 ]. Studies have already projected that there are likely to be increases in heat-related mortality, across the U.S., particularly under higher greenhouse gas emission scenarios [ 2 , 33 ].…”
Section: Discussionmentioning
confidence: 90%
“…Raised temperatures can lead to heat stress, heat stroke, and premature death as the body's temperature increases beyond its normal range of 36.0 to 37.5°C-hyperthermia (Schmeltz et al 2015;Knowlton et al 2007). The Center for Disease control estimates 8000 premature deaths between 1979 and 1999 were affected by excessive heat exposure (CDC 2007).…”
Section: Human Healthmentioning
confidence: 99%